Antioxidant Potential of Garlic (Allium sativum) Ethanol Extract in Gel Formulation Assessed by DPPH Method - dian novita (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
Garlic (Allium sativum) is known to have antioxidant activity that is beneficial to health. Antioxidant activity is expressed in IC₅₀ value, which is the concentration of the extract that can reduce 50% of free radicals. This study aims to test the antioxidant activity of a gel formulated from garlic extract using the DPPH (2,2-diphenyl-1-pyrrylhydrazine) method. The garlic extract and garlic gel extract were tested to evaluate the % inhibition and IC₅₀ values. Garlic ethanol extract showed an IC50 value of 89,290, and garlic ethanol extract gel showed the % inhibition value of 87,30. The decrease in the IC₅₀ value indicates that the gel formulation provides significant antioxidant activity against DPPH free radicals. In conclusion, the ethanol extract of Allium sativum formulated into a gel showed antioxidant activity based on IC₅₀ and percentage of inhibition values obtained from the DPPH assay.